Simple, fast and inexpensive method for determination of ranitidine hydrochloride based on conductometric measurements - Bindewald, Eduardo Henrique; Rosa-Sobrinho, João Carlos; Bergamini, Márcio Fernando; Marcolino-Júnior, Luiz Humberto (Eclética Química, 2018)
This work aims the development and optimization of an alternative method for ranitidine hydrochloride (RAN-HCl) determination. The proposed method was based on conductometric titration of RAN by precipitation of AgCl solid using a solution of AgNO3 as titrant. It was investigated the possibility of performing the titrations on hydroalcoholic and deionized water medium. A limit of detection of 1.0 mmol L-1 and 0.5 mmol L-1 were achieved for RAN titration in deionized water and in a 75:25 hydroalcoholic mixture, respectively. Such behavior is attributed to the dielectric constant of hydroalcoholic medium, which is lower than aqueous solution, making AgCl more insoluble and improving the resolution of the conductivity curve around the end point. Therefore, it is concluded that the conductometric titration method to determine RAN using AgNO3 as titrant proved to be feasible at low drug concentrations. The statistical calculations for obtained results suggested good precision for the conductometric method. According to t-test, there were no significant differences between found values at a 95% confidence level. Moreover, obtained results showed an excellent performance of the proposed method on quality control of RAN-HCl in generic formulations without any sample pretreatment.